Wpływ leczenia przeciwzapalnego na powodzenie terapii zespołu suchego oka - Mrukwa-Kominek, Ewa; Rogowska-Godela, Anna; Gierek-Ciaciura, Stanisława (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Dry eye syndrome is a common chronic disease; agents and strategies for its effective management are still lacking. The syndrome tends to be accompanied by ocular surface inflammation; therefore, the use of anti-inflammatory agents might prove beneficial. The authors present up-to-date guidelines, strategies, and efficacy of dry eye syndrome management, including antiinflammatory treatment. As no diagnostic tests are now available to assess ocular surface inflammation severity, the right timing to launch an antiinflammatory agent is difficult to determine. Patients with mild intermittent bouts of symptoms which can be alleviated with ophthalmic lubricants do not typically require anti-inflammatory therapy. The latter should be considered in those who do not respond to lubricating drops, obtain poor results on clinical tests, and show symptoms of ocular surface irritation (eg. conjunctivae redness). Anti-inflammatory treatment of dry eye syndrome may include short-term corticosteroids, cyclosporine A emulsion, oral tetracycline therapy, oral omega-3 fatty acid supplements, and autologous serum eye drops. Anti-inflammatory treatment should be safe and effective; potential benefits should be evaluated for each individual patient. The authors have reviewed the advantages of anti-inflammatory treatment in dry eye syndrome, presented in literature.